(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
This article examines the socio-political views of the Jadids, the first socio-political movement that embarked on the path of struggle for national independence in Turkestan was the movement of Jadidism. The Jadids proclaimed their main goal to build a secular democratic state by reforming its economic, political and cultural life, working out their own way of introducing the peoples of Central Asia to the achievements of world civilization.